إدارة بيئة اللغة العربية : تكوينا وتطبيقا - Wiwik Prasetiyo Ningsih; Mohammad Zainal Hamdy (Program Studi Pendidikan Bahasa Arab Institut Agama Islam Sunan Kalijogo Malang, 2021)
A good classroom cares a lot about a good environment for learning. A good environment is shown by creating a learning environment that is safe, comfortable, and organized, so that education can run smoothly. A good environment is very important so that students feel happy, their class shares optimism, their teacher is respected, and parents and the community feel welcome. A good environment encourages members of the environment to work and learn well, encourages a desire to learn, and helps students to develop their competencies, and all of these lead to success in education. It is known that not every Islamic school has all the factors of the physical and moral environment, and it is not in the teacher's ability to create them. Therefore, the teacher must take advantage of the environmental factors in his school to the best and maximum benefit, while constantly trying to increase them in quantity and quality. There is a way to benefit from the environment in promoting and improving the teaching of the Arabic language, including: Make your teaching attractive and interesting, and your speech eloquent, polite and soft. Commit to constantly using the Arabic language with your students, so that you will be a good example for them with prestige in their eyes. Reduce the explanation and statement and more instead of training, application, and so on.Keywords: Management, Environment, Arabic, Formation and Application